South of Eden : photographs et texts 1991-2016 - Ban, Andrej 1964-; Ban, Andrej 1964-; Steele-Perkins, Chris (Slovart, 2016)
"Afghanistan Albania Armenia Czech Republic Gaza Strip Georgia Greece Haiti Hungary Iran Israel Japan Kosovo Macedonia Naorno-Karabakh Pakistan Peru Poland Romania Serbia Slovakia Sri Lanka Tunisia Turkey Ukraine"--Cover. The photographer and reporter from the journal týžden. Andrej Bán is presenting 82 black-and-white documentary photographs from 25 countries, that he has visited in the last 25 years. Original snap-shots are completed by interesting stories about life in regions affected by wars, exoduses, ethnical and religious conflicts and natural disasters. Although pictures from disaster regions dominate the publication, the book is not only about horrors, but mainly about the hope and the ability of ordinary people to survive and cope with their destiny. The author of the book Andrej Bán comes back to Kosovo, Bosna and Hercegovina, Georgia, Pakistan, Afganistan, and other countries regularly.